The Effectiveness of Combination of The Bomb Method and Rolling Massage to Speed the Expenditure of Breast Milk - Nuryani Nuryani; Ayesha Hendriana Ngestiningrum; Astuti Setiyani (Aloha International Journal of Health Advancement (AIJHA), 2021)
Background: Breastmilk is the most important baby food, especially in the first months of a baby's life. The basic problem that often makes mothers feel confused and finally chooses other alternatives to meet the baby's needs. The issue of early breastfeeding has a negative impact on the life of the baby. The problem of expressing breastmilk on the first day after delivery can be caused by reduced stimulation of the hormone oxytocin and psychological factors. To help postpartum mothers with breastfeeding issues, considering that the success of exclusive breastfeeding is very much determined in the first days after delivery by developing a combination of the BOM Method and Rolling Massage to facilitate breastfeeding. Methods: The research design used was a quasi-experimental study with a post test only design with a control group. The study population of postpartum mothers in the Puskesmas Lembeyan area used consecutive sampling technique with independent variables. Combination of BOM and Rolling Massage methods, the dependent variable was the release of breast milk in postpartum mothers. Results: The results showed that the combination of the BOM method and the rolling massage technique was effective in increasing breastfeeding with a significant value of the Manova test of 0.000. The BOM method by massaging the breasts and expressing milk so that the reflex for the release of breast milk can be optimal. Combining the Rolling Massage method will stimulate milk production to help post-partum mothers expedite breastfeeding. Conclusion: The combination of the BOM method and the rolling massage method is very effective in accelerating breastfeeding, so it is necessary to apply this method to accelerate milk production, especially in the first days of post partum so that optimal breastfeeding can support the exclusive breastfeeding program. Keywords: combination of BOM method and rolling massage; breastfeeding expression